The Impact of Smoking on Poverty: Evidence from Indonesia - Arowadi Lubis; M. Reza Bukhori Ahmad; M. Ghafur Wibowo; Amalia Nur Zahra (Department of Development Economics, Universitas Sriwijaya, 2021)
This study investigates the impact of cigarette consumption on poverty incidents in Indonesia, control for Regional Gross Domestic Products, Consumption Credit, Human Development Index, and Unemployment. The data is obtained from the Bureau of Statistical Center (BPS) and the Financial Services Authority (OJK). The analysis is conducted by employing the Static Panel Data Model, namely Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Among the three, REM is the best model according to Chow and Hausman Test. The finding shows that cigarette consumption in Indonesia tends to worsen poverty, indicated by the positive and significant relationship between cigarette consumption and poverty in REM analysis. Moreover, RGDP also has a significant and positive effect on poverty. It means that RGDP is not able to reduce poverty in Indonesia. Hence, it can be concluded that the impact of cigarette consumption in increasing poverty outweighs the impact of cigarette production in decreasing poverty through RGDP.